Pengaruh Intensitas Modal dan Sales Growth Terhadap Penghindaran Pajak : Studi Empiris Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia 2019 – 2023 - Melati, Erma; Fahmi, Darul (Prisani Cendekia, 2025)
This study aims to analyze the effect of capital intensity and sales growth on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange. Tax avoidance is measured using the proxy of the ratio of cash tax payments to profit before tax. This research employs a quantitative approach with secondary data obtained from annual financial reports published through the official website of the Indonesia Stock Exchange. Data analysis was conducted using panel data regression with a random effects model, selected based on the results of the model specification test. The findings reveal that capital intensity has a significant effect on tax avoidance, whereas sales growth does not show a significant effect. These results provide implications for corporate management to optimize fixed asset management strategies, as well as for regulators in formulating more effective tax policies to minimize tax avoidance practices.